2020
DOI: 10.1038/s41598-020-75894-w
|View full text |Cite
|
Sign up to set email alerts
|

A biodegradable microneedle sheet for intracorporeal topical hemostasis

Abstract: Management of bleeding is critical for improving patient outcomes. While various hemostatic products are used in daily practice, technical improvement is still needed. To addresses this problem, we newly developed a microneedle hemostatic sheet based on microneedle technology. We demonstrated the unique features of this microneedle hemostatic sheet, including reduced hemostatic time, biodegradable polymer composition that allows intracorporeal use without increasing infectious risk incorporation of microneedle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Injectable hydrogels are based on in situ cross-linking of prepolymer solutions upon application to the wound site, which enable filling complex-shaped voids, full coverage of wounds, and integration with minimally invasive surgeries . Hydrogel beads also have shown the capacity for injectability and demonstrated the potential for hemostatic applications. ,, Fast gelation of injectable hydrogels is of great importance to seal the bleeding area physically. Wound dressings can be designed in the form of wet hydrogels, dry patches, and particles. , Hemostasis in wet hydrogels is mostly based on chemical interactions with blood plasma, whereas dry patches, in the form of membranes, microneedle arrays, , electrospun mats, textiles, sponges, and cryogels, as well as aerogels, can promote hemostasis through both plasma absorption and interactions with blood plasma components similar to hemostatic particles. Solutions of hemostatic particles can be sprayed for easier application on the wound site .…”
Section: Hemostatic Materials and Reagentsmentioning
confidence: 99%
“…Injectable hydrogels are based on in situ cross-linking of prepolymer solutions upon application to the wound site, which enable filling complex-shaped voids, full coverage of wounds, and integration with minimally invasive surgeries . Hydrogel beads also have shown the capacity for injectability and demonstrated the potential for hemostatic applications. ,, Fast gelation of injectable hydrogels is of great importance to seal the bleeding area physically. Wound dressings can be designed in the form of wet hydrogels, dry patches, and particles. , Hemostasis in wet hydrogels is mostly based on chemical interactions with blood plasma, whereas dry patches, in the form of membranes, microneedle arrays, , electrospun mats, textiles, sponges, and cryogels, as well as aerogels, can promote hemostasis through both plasma absorption and interactions with blood plasma components similar to hemostatic particles. Solutions of hemostatic particles can be sprayed for easier application on the wound site .…”
Section: Hemostatic Materials and Reagentsmentioning
confidence: 99%
“…Sometimes technically improved hemostats are necessary to enhance the efficacy and functions [ 116 , 223 ]. For example, Takagi et al [ 116 ] recently reported a gelatin-based two-layer sheet composed of gelatin sponge and gelatin sheet as a topical agent to stop bleeding.…”
Section: Various Forms Of Hemostat Devices From Biopolymersmentioning
confidence: 99%
“…Lately, microneedle technology has shown great promise in various applications, including drug and cell delivery [ 224 , 225 ]. Inspired by that, Yokoyama et al [ 223 ] developed a hemostatic sheet based on their microneedle technology. In addition, their microneedle hemostatic sheet can be potentially used in intracorporeal topical hemostasis for parenchymatous organs, major arteries and the heart wall following trauma or surgery.…”
Section: Various Forms Of Hemostat Devices From Biopolymersmentioning
confidence: 99%
“…In a previous study [ 63 ], uncoated and excipient-coated NanopatchTM vaccines were given to 18 healthy persons for 2 min of insertion and removal [ 33 , 368 , 370 ]. On a scale of 0 to 10, 78 percent of participants reported 0 on a pain range of 0 to 10, with an average score of less than 1 on a pain scale of 0 to 10 [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 …”
Section: Microneedle Array Patch Vaccination: Clinical Trials and Hum...mentioning
confidence: 99%